Analisis Keuntungan Pengusahaan Hutan Pinus (Pinus Merkusii Jung Et De Vriese) Di KPH Pekalongan Barat (The Pine (Pinus merkusii Jung et de Vriese ) Forest Plantation Rentability Analysis In KPH West Pekalongan) - Wahyu Andayani (Institut Pertanian Bogor (IPB University), 2006)
Economical value of the pine wood and resin in the last ten years has contributed significant revenue to the KPH West Pekalongan. This research is aimed to discover the optimum rotation of the development of forest pine to gain the maximum yield for the producer. The method used in this study is the analysis of the Land Expectation Value (LEV) by estimating the physical production function which developes the wood and resin at every plant rotation. The results of the analysis is that in the rotation of 20 years, the pine forest could produce maximum net yield/ net (profitability) /rentability from the sales of wood and resin, by using the real interest rate of 9,75% annually as follow : (a) In the third bonita is Rp. 1.546.945, 36/hectar/rotation and (b) in the fourth bonita is Rp. 2.032.392,56/hectar/rotation. By shortening the rotation from 35 years to 20 years, it results in the increasing yield of the forest pine plantation in KPH West Pakalongan of 6,1 % to 8,6% more than the real yield gained by the producer at present.Key words: Rentability, rotation, bonita, resin, LEV